2007
DOI: 10.4314/as.v5i2.1550
|View full text |Cite
|
Sign up to set email alerts
|

Poultry manure application and varietal effects of chilli-pepper (<i>Capsicum </i> species) on insect pests and disease in a humid-tropical environment

Abstract: Cultural practices such as organic manure application can affect soil fertility and also insect pest and disease incidence on the plant. The effect of poultry manure application was therefore evaluated in relation to the infestation by major insect pests and disease of pepper in a humid tropical agro-ecosystem. Treatments comprised three varieties of chilli pepper, Capsicum annum vars. tartashi and tarugu and Capsicum frutescens var. Birds eye chilli, and three Poultry Manure (PM) rates: 0, 20, and 40 t ha-1 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…The cash potentials from this study, combined with previous studies indicating that it is easy to grow, harvest and process, make yellow pepper suitable for use in poverty reduction (Dagnoko et al, 2013). In all the communities sampled a higher percentage of the farmers were females, making women a crucial resource in agriculture and rural economy (FAO, 2011 (Echezona and Nganwuchu, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cash potentials from this study, combined with previous studies indicating that it is easy to grow, harvest and process, make yellow pepper suitable for use in poverty reduction (Dagnoko et al, 2013). In all the communities sampled a higher percentage of the farmers were females, making women a crucial resource in agriculture and rural economy (FAO, 2011 (Echezona and Nganwuchu, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In the study also, some farmers claimed that chicken droppings, goat and cow dung have proved useful in plant protection, when sprayed on all green plants of vegetable and fruits. Earlier studies revealed that while the use of animal excrement may increase soil nutrient, and subsequently, increase plant growth, increased rates of poultry droppings, increased aphids (except B. tabaci), mired and grasshopper infestations as well as incidences and severities of pepper venial mottle virus (PVMV) symptoms, compared to where no manure was applied; but not (Echezona and Nganwuchu, 2006). Chicken droppings may have selective effects on the insect pests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the fruiting stage, plants with lower population densities were still more vigorous than those of higher population densities which may be, due to availability of space, assimilates and other micro-environmental components like air movements. It should also be noted that poultry manure was applied broad cast on equal measures per plot according to the suggestion by Echezona and Nganwuchu (2006). Therefore, plants with lower densities had more available nutrients which invariably were translated to higher vigor.…”
Section: Discussionmentioning
confidence: 99%
“…Although pepper can be grown all over Nigeria, the northern region between latitude 10 o N and 12 o N is the major area for production where an estimated 77,000 hectares of land under pepper cultivation yields about 695 000 metric tons [6]. The export attraction has encouraged pepper production in western Nigeria where production have been accompanied with a lot of research [1,2,7] and in the eastern region that even has special indigenous variety, "Nsukka yellow pepper" [8,9]. Literature is scarce for Capsicum spp.…”
Section: Introductionmentioning
confidence: 99%